2020
DOI: 10.3390/met10010126
|View full text |Cite
|
Sign up to set email alerts
|

Grain Refinement of Ti-15Mo-3Al-2.7Nb-0.2Si Alloy with the Rotation of TiB Whiskers by Powder Metallurgy and Canned Hot Extrusion

Abstract: In situ synthesized TiB whiskers (TiBw) reinforced Ti-15Mo-3Al-2.7Nb-0.2Si alloys were successfully manufactured by pre-sintering and canned hot extrusion via adding TiB2 powders. During pre-sintering, most TiB2 were reacted with Ti atoms to produce TiB. During extrusion, the continuous dynamic recrystallization (CDRX) of β grains was promoted with the rotation of TiBw, and CDRXed grains were strongly inhibited by TiBw with hindering dislocation motion. Eventually, the grain sizes of composites decreased obvio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…(2) An experimental method has been proposed to ascertain the relationship between the degree of deformation and the relative density of powder green samples in relation to compaction pressure and the duration of pressure application. This method applies to single-layer, double-layer, and multilayer materials based on Ti-B- (20,30,40) wt % Ti and TNM (at %: 51.85Ti-43Al-4Nb-1Mo-0.15B). (3) Rheological patterns were studied during cold uniaxial pressing of powder green samples depending on the composition of the initial components, height, and number of layers Ti-B- (20,30,40) wt % Ti and TNM (at %: 51.85Ti-43Al-4Nb-1Mo-0.15B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) An experimental method has been proposed to ascertain the relationship between the degree of deformation and the relative density of powder green samples in relation to compaction pressure and the duration of pressure application. This method applies to single-layer, double-layer, and multilayer materials based on Ti-B- (20,30,40) wt % Ti and TNM (at %: 51.85Ti-43Al-4Nb-1Mo-0.15B). (3) Rheological patterns were studied during cold uniaxial pressing of powder green samples depending on the composition of the initial components, height, and number of layers Ti-B- (20,30,40) wt % Ti and TNM (at %: 51.85Ti-43Al-4Nb-1Mo-0.15B).…”
Section: Discussionmentioning
confidence: 99%
“…Presently, a promising approach to increase heat resistance involves reinforcing intermetallic compounds based on titanium aluminides with various strengthening phases [12][13][14][15][16][17][18]. Among the strengthening phases employed, titanium monoboride stands out due to its closely matched coefficient of thermal expansion (7.2 × 10 −6 K −1 ) and excellent chemical and thermal compatibility with the TiAl matrix [19][20][21]. This fact makes titanium monoboride the most suitable candidate for the development of layered composite materials (LCMs) based on TiB/TiAl(Nb,Mo)B.…”
Section: Introductionmentioning
confidence: 99%
“…It was found out, among others, that Ti-6Al-4V with a globular microstructure is characterized by high strength and high plasticity in comparison to this alloy with a lamellar microstructure, whereas Ti-6Al-4V obtained via the powder metallurgy method reveals the highest plastic flow stress, with good plasticity at the same time. Hou et al [13] successfully manufactured TiB-whiskers-reinforced Ti-15Mo-3Al-2.7Nb-0.2Si alloys by adding TiB 2 powder and pre-sintering followed by canned hot extrusion. It was observed that the extrusion led to grain refinement and the strengthening of the composite, especially at the process temperature of 1000 • C. Powder-metallurgy-titaniumbased composites were also researched by Montealegre-Meléndez et al [14].…”
Section: Development Of Microstructure and Operational Propertiesmentioning
confidence: 99%
“…Simultaneously, strengthening depended linearly on volume fractions of TiBw with the premise of good interfacial bonding between TiBw and Ti matrix. Additionally, Hou et al [10] studied the grain refinement of in situ synthesized TiBw in the TiBw/Ti-15Mo-3Al-2.7Nb-0.2Si composites by low energy milling, pre-sintering and canned hot extrusion. Feng et al [8], Chen et al [9] and Hou et al [10] obtained expected results in above studies; however, the process and growth of TiBw during sintering were not investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Hou et al [10] studied the grain refinement of in situ synthesized TiBw in the TiBw/Ti-15Mo-3Al-2.7Nb-0.2Si composites by low energy milling, pre-sintering and canned hot extrusion. Feng et al [8], Chen et al [9] and Hou et al [10] obtained expected results in above studies; however, the process and growth of TiBw during sintering were not investigated. Harshpreet Singh [11] studied that TiB grows preferentially via the one-way dispersion of B atoms mostly along the [010] direction because of the steadiness of the B-B bonds in the [010] direction.…”
Section: Introductionmentioning
confidence: 99%